PKM WAWASAN APLIKASI MATEMATIKA DI DUNIA KERJA TERHADAP PENINGKATAN MINAT SISWA DALAM BERMATEMATIKA - Susila Bahri; Lili Fajria; Syofyan Syofyan (Jurnal Abdimas Bina Bangsa, 2023)
The minimal knowledge of the students of SMAN 3 Pariaman about the use of mathematics in various professions resulted in these students needing to be made aware of the importance of learning and understanding mathematics. This lack of awareness also has an impact on interest in mathematics. From the questionnaire results with a sample of 50 students of SMAN 3 Pariaman, it was found that initially, only 10% of students were interested in mathematics. Then to increase students' interest and insight into the application of mathematics through socialization is carried out on various examples of cases or problems in the world of work which are solved using high school mathematics material. From the results of the questionnaire at the end of the socialization, it was found that there was an increase in the number of students who were interested in mathematics by 26%. It shows that the explanation about using mathematics material significantly influences students' interest and insight in mathematics